Ministerial Decree No. 828/2017 On Amending Some Provisions of the Ministerial Decree No.8180/1996 on Organizing Foreigners' Residence Inside The Arab Republic of Egypt = القرار الوزاري رقم 828 لسنة 2017 بتعديل بعض أحكام القرار الوزاري رقم 8180 لسنة 1996 بتنظيم إقامة الأجانب بأراضي جمهورية مصر العربية / Prime Minister - Egypt. Prime Minister (2025)
ministry of Interior decree no. 828 of the year 2017 on amending some Provisions of the ministerial decree no. 8180 of the year 1996 on organizing foreigner’s residence inside the Arab republic of Egypt وزارة الداخلية قرار رقم 828 لسنة 2017 بتعديل بعض أحكام القرار الوزارى رقم 8180 لسنة 1996 بتنظيم اقامة الاجانب بأراضى جمهورية مصر العربية